ANALISIS EMPIRIS FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT DENGAN ETIKA PROFESI SEBAGAI VARIABEL MODERASI - Wiwi Idawati; Shella Rachma Putri (BAJ: Behavioral Accounting Journal, 2020)
The purpose of this research is to examine the influence of work experience and audit fees and professional ethics as moderating variables on audit quality. This research is important to do again because of the inconsistency of the results of previous research and the increasing demands of users of financial reports for quality audit reports. Sampling was conducted using simple random sampling method with a sample size of 50 auditors from 17 public accounting firms in South Jakarta. The collection method uses a questionnaire method that is distributed to respondents. The data analysis technique of this research is using multiple regression analysis and moderation regression analysis. The results showed that work experience had an effect on audit quality while audit fees had no effect on audit quality. Professional ethics do not moderate work experience on audit quality, but professional ethics do moderate and weaken audit fees on audit quality. Work experience and audit fees simultaneously affect audit quality.